2021
DOI: 10.3390/su14010271
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Literature on Food Values and Their Potential Implications for Consumers’ Food Decision Processes

Abstract: This article offers a semi-systematic literature review on the concept of food values. Specifically, 36 relevant research articles were analyzed. The results underscore the novelty and rapid popularity of this concept in different professional, scientific, and academic fields. Among the findings, the article highlights how the concept of food values has evolved to accommodate the features and behaviors of specific markets. Nonetheless, one can group food values into three distinct clusters. This article expand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This has been accompanied by increased public knowledge and awareness about food safety [5][6][7]. Taste, price, safety, appearance, comfort, nutrition, naturalness, origin, tradition, fairness, and environmental impact are physical attributes that become the basic food value sets of consumers' choices [8]. Béné et al (2019) and Velten et al (2015) showed that sustainable agriculture incorporates production systems that protect the environment, public health, human communities, and animal welfare [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This has been accompanied by increased public knowledge and awareness about food safety [5][6][7]. Taste, price, safety, appearance, comfort, nutrition, naturalness, origin, tradition, fairness, and environmental impact are physical attributes that become the basic food value sets of consumers' choices [8]. Béné et al (2019) and Velten et al (2015) showed that sustainable agriculture incorporates production systems that protect the environment, public health, human communities, and animal welfare [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A value system can guide consumer's food behavior. A literature review 72 on food values and their potential implications for consumers’ food decision processes revealed three distinct clusters: (1) credence (environmental impact, origin, and fairness), experience (taste, appearance, convenience, and novelty), and price paid (price), (2) beneficial value (taste, price, nutrition, and appearance), social value (restauration, employment creation, origin, and environment), safety value (food inspection methods), (3) product value (texture, color, and freshness), process value (production and processing practices, environmental impact, naturalness, and animal welfare), location value (setting of food purchase or consumption), and emotional value (feel-good factor, experience, entertainment, indulgence, and consumption of specific foods or brands). Process values are particularly relevant in shaping consumer behavior as they include consumers’ ethical concerns about the production processes, fast-changing technological innovations, animal welfare and environmental pollution.…”
Section: Drivers Of Food Wastagementioning
confidence: 99%